INCREASING OF KNOWLEDGE AND ATTITUDE OF WOMEN IN MEETING THE NUTRITION DURING PREGNANCY THROUGH HEALTH PROMOTION - Andri Setiya Wahyudi; Ira Suarilah Suarilah; Elyk Dwi Mumpuningtias; Mery Fuji Astutik (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2016)
Introduction: Pregnancy lead to changes in anatomical, physiological, and biochemical. Changes of it affect the nutritional needs of pregnancy. Knowledge and a bad attitude will affect the nutritional needs of pregnancy.  This research aims to know the affect of health promotion of the knowledge and attitude of mother in fulfillment of nutrition during pregnancy in Paberasan village. Method: The quasy experiment with pretest posttest control group design. The amount of pregnant in Paberasan village were 32 people. Analysis using the Wilcoxon Signed Rank test and Mann-Whitney. Result: The result showed that, the treatment group before given health promotion the majority have enough knowledge (81,25%). After given health promotion all of respondent have good knowledge (100%). The attitude of pregnant before given health promotion the majority have enough attitude (68,75%). After given health promotion the majority have good attitude (68,75%). In the control group before given health promotion the majority have knowledge enough (75%). The control group obtained the results of the knowledge tends to remain. The attitude of pregnant before given health promotion majority has enough attitude (62,50%). The control group obtained the result of the attitude tends to remain. Mann-Whitney test results obtained significant value p=0,000 less than 0.05. Attitude test results before and after treatment in the treatment group and the control group obtained significant value p = 0.001 less than 0.05. The results showed that there is effect of health promotion of the knowledge and attitudes of mothers in fulfillment of nutrition during pregnancy. Discussion: Health workers in Paberasan village to give health promotion about the fulfillment of nutrition during pregnancy to the community to help improve the knowledge of society and help realize the achievement of fulfillment of good nutrition during pregnancy. Keyword: Promotion, health, nutrition, pregnant, knowledge, attitudes, Paberasan, Sumenep